Desempenho do maracujazeiro-azedo, BRS rubi do Cerrado, enxertado sob diferentes porta-enxertos - Ferreira, Luciano Gomes (2021)
Fusariosis, a disease caused by Fusarium oxysporum, causes premature death of plants, reducing the useful life of the orchard, making its cultivation unfeasible. The use of grafted seedlings has been an alternative in areas with a history of occurrence of this disease. However, different combinations between grafts and rootstocks can influence the development, production and longevity of the orchard. The objective of this work was to evaluate the development, flowering, fruiting, production and mortality of passion fruit plants of the commercial cultivar BRS Rubi do Cerra-do pé franco and grafted under three species of Passifloras rootstocks, in an area with a history of the occurrence of fusariosis, in Terra Nova do Norte, State of Mato Grosso. The design was that of blocks, at random, with 4 treatments: the cultivarvar BRS Rubi do Cerrado pé-franco (control), and grafted in three species of rootstocks: Passiflora gibertii, P. alata and P. nitida, with 6 repetitions, totaling 24 plots, with 8 plants each. The seedlings were produced in the screened nursery (shaded at 50%) at COOPERNOVA in Terra Nova do Norte-MT, and the grafting was done by forking a slit filled top. Planting was carried out at 70 days after grafting, with a spacing of 3 m between plants and 3 m between rows, and the plants were guided in a vertical spreader. The graft setting, plant height growth, stem diameter below and above the grafting point, flowering and fruiting, number, total and average weight of fruits, productivity and plant mortality were evaluated. Disease progress curves and plant mortality data were plotted over 8 periods between 214 and 484 days after planting (DAP). With these data, it was estimated, the area under the disease progress curve (AACPD), used to observe an epidemic. The AACPD data were subjected to statistical analysis, with the means compared by the Scott Knott test, at the level of 5% probability, and the diameter data compared by the Tukey test (p≤0.05). There was compatibility between the species with extraction setting above 98%. The free-standing plants and grafted on P. giberti had higher growth in height, flowering and fruiting. Between 120 and 187 (DAP) the diameters doubled in all plants. Flowering started at 120 (DAP) and 180 (DAP), more than 70% of the plants fruited, with no differences in fruiting, this time being an indication of the start of production for these combinations. The cultivar BRS Rubi do Cerrado grafted on P. gibertii and P. nitida, showed higher productivity in relation to free-standing. The cultivar grafted on P. alata, P.gibertii and P. nitida had the highest number of fruits and P. giberti had the highest average weight of fruits. The cultivar grafted on P. nitida, showed zero mortality during 16.5 months of cultivation. The rootstocks P. nitida and P. gibertii were superior to P. alata in reducing passion fruit mortality from Fusarium oxysporum f. passiflorae. The pathogenicity of Fusarium oxysporum f. passiflorae, isolated from seedlings of cultivar Rubi inoculated at 70 days of age.